Analisis Pertumbuhan Ekonomi, Jumlah Penduduk dan Indeks Pembangunan Manusia terhadap Distribusi Pendapatan di Aceh Bagian Timur - Fadillah; Puti Andiny; Rinaldi Syahputra (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This research aims to determine the influence of Economic Growth, Population and Human Development Index on Income Distribution in Eastern Aceh simultaneously and partially in 2012-2021. This research uses time series data using panel data regression analysis method. E-Views application version 10, which produces a coefficient value for the Economic Growth variable of 0.9402 and has an insignificant effect on Income Distribution. The population coefficient value is 0.5946 and has insignificant effect on Income Distribution. The coefficient value of the Human Development Index is 0.0006 and has an effect significant to Income Distribution. The coefficient of determination (R2) is 0.6948 or 6948%. Meanwhile, the remaining 30.16% was influenced by other factors not examined in this research.